Bisphenol-A Leaching from Polycarbonate 5-Gallon Water Bottles in the UAE: A Comprehensive Study (Nepal Journal of Epidemiology, 2024)
Bisphenol-A (BPA), a key component in the production of Polycarbonate (PC) plastics, is used extensively worldwide. Notably, the ubiquitous 5-gallon water bottles in the UAE are primarily made of PC plastic, making them a significant concern as bottled water is a primary source of drinking water in the region. These bottles undergo temperature variations during storage and transportation, potentially leading to harmful BPA leaching.This study analyzed 40 PC 5-gallon water bottles from two local brands A and B, with 20 bottles per brand, under two conditions: room temperature and outdoor sunlight exposure for a month. BPA levels were assessed at 0, 15, and 30 days, following ethical approval. Liquid-liquid extraction and ELISA assays were conducted, with comprehensive kit validation.The results revealed a significant increase in BPA concentration over time, particularly in bottles exposed to elevated temperatures (Day 30 outdoor-stored samples exhibited the highest concentration at 9.05 ± 2.30 μg/L). Brand B consistently exhibited higher BPA concentrations across different samples and environments.This study emphasizes the relationship between BPA concentration and storage duration, highlighting the need for preventive measures to reduce BPA exposure. Individuals should be aware of potential health risks associated with prolonged storage in plastic containers and consider safer alternatives.